Backscattering Properties of Nonspherical Ice Particles Calculated by Geometrical-Optics-Integral-Equation Method - Masuda Kazuhiko; Ishimoto Hiroshi; Sakai Tetsu; Okamoto Hajime (EPJ Web of Conferences, 2016)
Backscattering properties of ice crystal models (Voronoi aggregates (VA), hexagonal columns (COL), and six-branched bullet rosettes (BR6)) are calculated by using geometrical-opticsintegral-equation (GOIE) method. Characteristics of depolarization ratio (δ) and lidar ratio (L) of the crystal models are examined. δ (L) values are 0.2~0.3 (4~50), 0.3~0.4 (10~25), and 0.5~0.6 (50~100) for COL, BR6, and VA, respectively, at wavelength λ=0.532 μm. It is found that small deformation of COL model could produce significant changes in δ and L.